2015
DOI: 10.1007/s00384-015-2321-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pathological response of the mesorectal positive nodes between short-course chemoradiotherapy with delayed surgery and long-course chemoradiotherapy in patients with rectal cancer

Abstract: The tumor regression effect of LC-CRT on the primary tumor and positive nodes was more favorable than SCRT-delay, and LC-CRT is able to predict the LRG 3 response with a high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This result suggests that presence of fibrosis and/or necrosis in the LN is a signature of lymph node metastasis before CRT. Beppu et al demonstrated that metastasis-negative LNs were histologically distinguishable from total regression LNs (metastasis-positive LNs before treatment), because metastasis-negative LNs with rectal cancer were filled with normal lymph nodules (8). Similarly, our current study revealed that the normal LN structure was maintained, with neither fibrosis nor necrosis, in resected LNs that were diagnosed as having no metastasis before CRT.…”
Section: Discussionsupporting
confidence: 69%
“…This result suggests that presence of fibrosis and/or necrosis in the LN is a signature of lymph node metastasis before CRT. Beppu et al demonstrated that metastasis-negative LNs were histologically distinguishable from total regression LNs (metastasis-positive LNs before treatment), because metastasis-negative LNs with rectal cancer were filled with normal lymph nodules (8). Similarly, our current study revealed that the normal LN structure was maintained, with neither fibrosis nor necrosis, in resected LNs that were diagnosed as having no metastasis before CRT.…”
Section: Discussionsupporting
confidence: 69%
“…Given the different combination schemes of dose fractionation and time to surgery, a goal interval of 6–8 weeks is the most commonly used value in clinical trials [Figure 2(a)]. 5,15,17,18,21,24,27,28,31,32,3436,3842,44,4648,50,52,5594 Moreover, because of factors such as acute radiation reaction, there are some discrepancies between the goal intervals and true intervals. 95 Despite limited samples, a linear correlation can be observed between them in Figure 2(b).…”
Section: The Era Of 3d-crtmentioning
confidence: 99%
“…In the pathologic examination of the resected specimens, we followed the Japanese Clinical and Pathological Guidelines for the Colon, Rectum and Anus 7th edition. 11 As described previously, 12,13 this can be summarized as follows: the lymph nodes were harvested by palpation and fresh specimens were inspected visually without the use of a cleaning solution. After the harvesting of the lymph nodes, the operative specimens were fixed in 10% buffered neutral formalin for approximately 24-48 hs.…”
Section: Methodsmentioning
confidence: 99%